ЕКИНШИ ЖЕР ЖҮЗЛИК УРЫС ЖЫЛЛАРЫ ҚАРАҚАЛПАҚСТАН БАСПАСЫНДА ЖАЗЫЎШЫ ШАЙЫРЛАРЫНЫҢ ДӨРЕТПЕЛЕРИ - Қабулова, М.Т. (ILIM hám JÁMIYET, 2022)
The article reveals the images of Karakalpak writers during the Second World War. It is written about the collections of writers’ war-motivated works published during the war. The newspaper "Kyzyl Karakalpakstan" also reported that it played a significant role in raising public awareness.